Effect of the Atmosphere on Physical Optical and Luminescence Properties of Li2O:Y2O3:B2O3:CeF3 Glasses - W. Wongwan; K. Boonin; H. J. Kim; P. Limsuwan; J. Kaewkhao (Integrated ferroelectrics, 2021)
In this research intended to fabricate and develop an electrical furnace as the vacuum systems for melting glass by normal melt quenching technique under vacuum atmosphere. The 60Li2O: 10Y2O3: 29.5 B2O3: 0.5CeF3 glass system was prepared by this furnace. The properties of glass that prepare in air and vacuum atmosphere and comparative studied various properties such as physical, optical, luminescence. The result has shown that the density and refractive index was slightly decrease. The absorption edge of vacuum sample was shifted to shorter wavelength. The indirect and direct band gap of the vacuum glass sample higher than the air atmosphere glass sample which corresponded to the molar volume increase representing the enhancement of non-bridging oxygen (NBO) number in glass network. The photoluminescence of glass which preparing in vacuum was higher than in air about 2 times while the decay time are 101.83 ns (air) and 88.72 ns (vacuum), respectively.
Keywords: Glass properties and applications; Luminescence Properties of Advanced Materials; Digital Radiography and Breast Imaging